Baby boomers, age, and beauty - Woodspring, Naomi (Emerald Publishing Limited, 2018)
Drawing from a variety of sources from ageing research, history and gender studies, this book is a rich exploration of the baby boomers - those coming of age in the sixties and now entering old age - the influences that have shaped how they perceive ageing appearance, define ageing and beauty, and the meaning of appearance, beauty, and identity.